Manipulation of lipid content in algae biomass at the Blue Lagoon R&D Center - Máté Osvald 1992- (2015)
Microalgae have long been recognized as a potentially good source for biofuel production because of their high oil content and rapid biomass production. There are two main objectives of this research: one is to explore the effect of growth conditions on the lipid content in algae biomass and the other is to convert the algae biomass into lipid by using so-called hydrothermal liquefaction, (HTL, a process where long chain polymers of hydrogen, oxygen and carbon decompose into short-chain petroleum hydrocarbons, under heat and high pressure). The optimal circumstances for the HTL both in terms of temperature, pressure and running time during the HTL were investigated, with the aim maximizing the lipid content. Microalgae strain, isolated from the geothermal environment of the Blue Lagoon in Iceland was cultivated at the Blue Lagoon R&D Center in geothermal seawater. Algae were harvested and subsequently processed by HTL by exposing the algae to high pressure (more than 50 bar) and high temperature (up to 270 °C) at the same time, to achieve the chemical conversion of the biomass. An induction-heated autoclave, available from a previous M.Sc. project carried out at the Blue Lagoon R&D Center, was used. To investigate the highest amount of lipids naturally accumulated in the microalgae cells, growth conditions (nutrition concentration and pH) were manipulated in small-scale bioreactors. As the best outcome, oil content increased to 9.03% from the initial 0.46% in algae biomass, during hydrothermal processing at 280 °C temperature and under 56-61 bar pressure. This research confirmed that, microalgae cultivated with low nutrition concentration has the most lipid content per produced mass. However, unfavorable circumstances are limiting the growth rate of the biomass in a way, the absolute mass of produced lipids in are the lowest in the case of nutrition limitation. The thesis also gives an overview of geothermal systems and the most common methods and technologies used to harness geothermal energy.